Hubungan Beberapa Karakteristik Ibu Dari WUS Dan Lingkungan Masyarakat Dengan Kejadian Perkawinan Usia Dini Di Kecamatan Guntur Kabupaten Demak Bulan Januari-Maret Tahun 2013 - Nur Bayti Ikhsanita; S.A. Nugraheni; Raden Djoko Nugroho (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Corelation Of Some Factors Of Mothers Of Women At Productive Age And People Surrounding Factors To The Practice Of Early Age Marriage In Guntur Subdictrict Demak District Period January-March In 2013: Early age marriage is a marriage that is done at the age less than 20 years old for woman and less than 25 years old for man. Early age marriage does not support the effort for improving woman health as well as her reproduction right. As the result, early age pregnancy occurs along with high risk of miscarriage even more complication of abortion. The purpose of this study was to analyse the correlation of some factors in mothers of women at productive age and people surrounding factors with the phenomena of early age marriage. Method applied here was explanatory research with cross sectional study. The population was all women at productive age in Guntur sub district as many as 17,667 persons and there were 67 persons who was selected by using simple random sampling. The test data was using exact test with 5% rate. The result of this study showed factors that related to this were religion of women at productive age’s mothers (p=0.04), health reproduction knowledge of women at productive age’s mothers (p=0.001), and marriage culture of women at productive age’s mothers (p=0.001). While factors that were not related were mass media/ information (p= 0.73), education of women at productive age’s mothers (p=0.10) and social economy of women at productive age’s mothers (p=1.00), and people surrounding factors that were marriage culture in society (p=0.10). It is suggested that socialisation from Ministry of Religion and BKKBN about the maturity of marriage age to women at productive age is held continually by counselling interactively and including interactive simulation so that the knowledge about marriage in women at productive age can improve well in order to prevent the practice of early age marriage in Guntur sub district